Right to Work for Wives and its Implementation: Study of Gender Verses in Contemporary Indonesian Interpretation - Hanifatunnaza, Hanifatunnaza; Baihaqi, Yusuf (Westscience Press, 2025)
This research discusses the right to work for wives and its implementation of the formation of the sakinah family in the perspective of contemporary interpretation. With the development of the times, many women work in the public sector to help the family economy. However, this phenomenon has various impacts, both positive and negative, on household life. This study uses a qualitative approach with a literature study method, referring to contemporary interpretations such as Tafsir Al-Mishbah by M. Quraish Shihab. The results of the study show that Islam does not prohibit women from working, as long as they continue to fulfill their responsibilities in the family and maintain religious and moral values.